Analisis Yuridis Tentang Pertimbangan Hakim dalam Memberikan Izin Poligami bagi Pegawai Negeri Sipil (PNS) Wanita Sebagai Istri Kedua: Studi Putusan Nomor 0085/Pdt.G/2019/PA/Sel - Dalimunthe, Nuh Ansa; Milhan, Milhan (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the decision of the Religious Court Number 0085/Pdt.G/2019/PA.Sel regarding the application for polygamy permit with the second prospective wife a Civil Servant (PNS). This study is conducted to find out the basis for the judge's consideration of granting the application. Whereas as in Government Regulation Number 45 of 1990 Article 4 paragraph (2) does not allow female civil servants to become the second, third and fourth wives. This research is a type of qualitative research with a normative juridical approach that uses a statute approach, case approach, and literature approach. The primary data sources of this research are the Religious Court Decision 0085/Pdt,G/2019/PA.Sel, Marriage Law Number 1 of 1974, Government Regulation Number 45 of 1990 amending Government Regulation Number 10 of 1983, and the Compilation of Islamic Law (KHI). The results of this study indicate that the judge in exploring and adjudicating this case made ijitihad which granted a polygamy permit application with a prospective Civil Servant wife. The judge prioritized the principle of public justice as intended by Article 5 of Law Number 48 of 2009 concerning Judicial Power. The panel of judges also emphasized the morality aspect in which the applicant was allowed to marry (Polygamy). Because mutual love is difficult to separate, and the second wife candidate attaches a letter to bear the risk in Decision Number 0085/Pdt.G/2019/PA.Sel. Keywords: Polygamy, Juridical Analysis of Judges' Considerations, Female Civil Servants